Faktor – Faktor yang Mempengaruhi Pengalaman Pelanggan, WOM, Nilai yang Dirasakan, dan Kesadaran Merek Terhadap Niat Pembelian Ulang Pada Konsumen UNIQLO di DP Mall Kota Semarang - Dinda Selvi Aulia; Yohan Wismantoro; Mahmud Mahmud; Fakhmi Zakaria (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the influence of Customer Experience, Word of Mouth, Perceived Value, and Brand Awareness on the Repurchase Intention of Uniqlo consumers at DP Mall Semarang. This research employs a quantitative approach using a survey method involving 136 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4.0. The results indicate that all independent variables, namely Customer Experience, Word of Mouth, Perceived Value, and Brand Awareness, have a positive and significant effect on Repurchase Intention. Among these variables, Word of Mouth and Brand Awareness are the most dominant factors influencing repurchase intention. The R-square value of 0.782 suggests that the research model has strong explanatory power for the dependent variable. These findings imply that improving customer experience, consumer-to-consumer communication, perceived value, and brand awareness simultaneously can enhance consumers’ intention to repurchase.